Surgery-first orthognathic treatment of an adult patient with unilateral cleft lip-palate and multiple missing teeth: a case report - Hasibe, Baser Keklikci; Nisa, Gul Amuk; Alper, Alkan (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2019)
Introduction: The comprehensive treatment approach and outcomes of a patient with cleft lip and palate was presented in this casereport.Case presentation: A 31-year-old man with unilateral cleft lip and palate(UCLP) had a chief complaint of his mandibular prognathism andasymmetric smile. His clinical and radiographic evaluation showed a Class III skeletal relationship, multiple missing teeth, mandibularanterior occlusal canting, 6 mm of negative overjet and 16 mm overbite. "Surgery first orthognathic approach" was planned including,short-term orthodontic treatment, maxillary advancement and segmental mandibular subapical osteotomy.Conclusion: At the end of the treatment, a functional occlusion, a harmonious profile, and patient satisfaction were achieved.